Imaginarios sociales y proyectos de vida de los adolescentes del recinto Las Minas, provincia Bolívar, año 2023. - Velasco Carvajal, Jairo Rene (2024)
Social imaginaries are those symbolic systems that are built based on the experiences of social agents, but also on the construction of aspirations and interests, which is why a matrix of connections is established between various elements: such as the experiences of each individual, which contain: beliefs, feelings, images, ideas and common projects within a sociocultural context. Those elements that build the social imaginaries have a direct impact, mainly on boys, girls and adolescents, which is why the aim is to investigate and demonstrate which social imaginaries are that influence and predominate in the aspirations of the adolescents of the Las Minas Campus. the Bolívar province. Having said the above, this study will explore the social imaginaries of the adolescents of the Las Minas campus, and how these imaginaries intervene in the construction of their life projects. Therefore, research will be carried out through surveys of adolescents between 12 and 18 years of age. Through the content analysis of the bibliography, themes related to the social imaginaries and life projects of adolescents will be identified, the results will allow us to reflect on the importance of considering social imaginaries and how these can provide information in the planning and development of public policies and programs aimed at adolescents living in rural environments. Key words: Social imaginaries, Personal aspirations, Adolescents, rurality.